Marketing education and the employability challenge. (23rd February 2017) - Anderson, Deborah; Lees, Rebecca
Abstract: A major external challenge faced by UK higher education institutions is employability. For some academics, this poses a challenge and many feel it is not their role to help students acquire the generic employability attributes required in the workplace. In this paper, we demonstrate how innovative teaching practice at a UK Business School has ensured the development of good marketing subject learning, whilst at the same time has provided students with an opportunity to acquire generic employability attributes. This has been achieved by approaching an academic staple: the literature review as a series of well-designed tasks in which students learn through participation in rather than individually. The approach is based on a social practice framework and contributes to assertions in the literature that good learning can lead to good employability.